2021
DOI: 10.1007/s40271-021-00511-5
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Perspectives of Patients with Non-HIV-Associated Lipodystrophies and Their Caregivers: A Qualitative Study

Abstract: Background Lipodystrophy comprises a group of conditions characterized by loss of functional adipose tissue, resulting in severe metabolic complications and a complex range of symptoms. Objective This study sought to gain a holistic understanding of the impact of congenital or non-human immunodeficiency virus acquired lipodystrophies on the quality of life of patients and their caregivers and to capture the impact of lipodystrophy on quality of life using a standard ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…Our findings are in agreement with a qualitative analysis by Arpana et al that also indicated a significant number of patient-centered impacts associated with lipodystrophy, including significant hunger, pain, fatigue, depression, altered physical appearance, and anxiety [ 16 ]. While not a focus of the present study, our findings demonstrated that emotion/affect were often called out by patients with lipodystrophy.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in agreement with a qualitative analysis by Arpana et al that also indicated a significant number of patient-centered impacts associated with lipodystrophy, including significant hunger, pain, fatigue, depression, altered physical appearance, and anxiety [ 16 ]. While not a focus of the present study, our findings demonstrated that emotion/affect were often called out by patients with lipodystrophy.…”
Section: Discussionsupporting
confidence: 92%